Biochemical and Microbiological Characterization of a Thermotolerant Bacterial Consortium Involved in the Corrosion of Aluminum Alloy 7075 - Blamey-Alegria, J (Springer Science and Business Media B.V., 2024)
Microorganisms can play a significant role in material corrosion, with bacterial biofilms as major participants in microbially influenced corrosion (MIC). The exact mechanisms by which this takes place are poorly understood, resulting in a scarcity of information regarding MIC detection and prevention. In this work, a consortium of moderately thermophilic bacteria isolated from a biofilm growing over aluminum alloy 7075 was characterized. Its effect over the alloy was evaluated on a 40-day period using Electron Microscopy, demonstrating acceleration of corrosion in comparison to the abiotic control. The bacterial consortium was biochemically and microbiologically characterized as an attempt to elucidate factors contributing to corrosion. Molecular analysis revealed that the consortium consisted mainly of members of the Bacillus genus, with lower abundance of other genera such as Thermoanaerobacterium, Anoxybacillus and Paenibacillus. The EPS polysaccharide presented mainly mannose, galactose, rhamnose and ribose. Our observations suggest that the acidification of the culture media resulting from bacterial metabolism acted as the main contributor to corrosion, hinting at an unspecific mechanism. The consortium was not sulfate-reducing, but it was found to produce hydrogen, which could also be a compounding factor for corrosion. © 2023, The Author(s), under exclusive licence to Springer Nature B.V.